Rapid Synthesis and Sintering of Metals from Powders. Issue 12 (8th March 2021) - Wang, Chengwei; Zhong, Wei; Ping, Weiwei; Lin, Zhiwei; Wang, Ruiliu; Dai, Jiaqi; Guo, Miao; Xiong, Wei; Zhao, Ji‐Cheng; Hu, Liangbing
Abstract: Powder to bulk processes, such as additive manufacturing and metal injection molding (MIM), have enabled great potential for complex metal designing and manufacturing. However, additive manufacturing process normally introduces a high residue stress and textures due to the locally intense temperature. MIM is an excellent batch manufacturing process; nevertheless, it is not suitable for rapid screening and development of new metal compositions and structures due to the slow sintering process. Herein, an ultrafast high‐temperature sintering (UHS) process is reported that enables the rapid synthesis and sintering of bulk metals/alloys and intermetallic compounds. In this process, elemental powders are mixed and pressed into pellets, followed by UHS sintering in just seconds at a temperature between 1000 and 3000 °C. Three representative compositions, including pure metals, intermetallics, and multielement alloys, are demonstrated with a broad range of melting points. The UHS process for metal sintering is nonmaterials specific, in addition to being extremely rapid, which make it suitable for materials discovery. Furthermore, the sintering method does not apply pressure to the samples, making it compatible with 3D printing and other additive manufacturing processes of complex structures. This rapid sintering technique will greatly facilitate the development and manufacturing of metals and alloys. Abstract : An ultrafast high‐temperature sintering (UHS) process is developed to sinter a wide range of metals/alloys from compacts of elemental or prealloyed powders. Joule‐heated carbon heaters provide a uniform high‐temperature environment (up to 3000 °C) for a rapid sintering in just ≈10 s.